2021
DOI: 10.3389/fonc.2021.734594
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Sacituzumab Govitecan for the Treatment of Metastatic Triple-Negative Breast Cancer in China and the US

Abstract: BackgroundThe effectiveness of Sacituzumab Govitecan (SG) for metastatic triple-negative breast cancer (mTNBC) has been demonstrated. We aimed to evaluate its cost-effectiveness on mTNBC from the Chinese and United States (US) perspective.MethodsA partitioned survival model was developed to compare the cost and effectiveness of SG versus single-agent chemotherapy based on clinical data from the ASCENT phase 3 randomized trial. Cost and utility data were obtained from the literature. The incremental cost-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…In particular, PARP inhibitors improved prognosis in metastatic BRCA mutated patients [165,166] and are under evaluation in the neoadjuvant setting; TRK inhibitors showed activity and are approved in rare metastatic breast cancers harboring NTRK fusions and progressing despite previous treatment [171,172]; sacituzumab govitecan, based on the results of the phase III ASCENT trial, showed a PFS of 5.6 months compared to 1.7 months for patients who received chemotherapies of physician's choice, and received accelerated FDA approval for pretreated and advanced metastatic TNBC [184]. However, some criticism arose around the results and the cost/effectiveness ratio of this trial [227,228]. PI3K/Akt/mTOR and EGFR inhibitors as well as antiandrogens showed promising results and are under evaluation in Phase II/III clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PARP inhibitors improved prognosis in metastatic BRCA mutated patients [165,166] and are under evaluation in the neoadjuvant setting; TRK inhibitors showed activity and are approved in rare metastatic breast cancers harboring NTRK fusions and progressing despite previous treatment [171,172]; sacituzumab govitecan, based on the results of the phase III ASCENT trial, showed a PFS of 5.6 months compared to 1.7 months for patients who received chemotherapies of physician's choice, and received accelerated FDA approval for pretreated and advanced metastatic TNBC [184]. However, some criticism arose around the results and the cost/effectiveness ratio of this trial [227,228]. PI3K/Akt/mTOR and EGFR inhibitors as well as antiandrogens showed promising results and are under evaluation in Phase II/III clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the cabozantinib is not available in the mainland Chinese market now. Like some other cost-effectiveness investigations ( Chen et al, 2021 ), we used the Hongkong price in our study as many mainlanders would go to Hongkong for some unavailable drugs due to the lower prices and easy accessibility. Probabilistic sensitivity analysis showed that cabozantinib had a 50% likelihood to be cost-effective when its price dropped to ¥5.87/mg, near one-third of its current price.…”
Section: Discussionmentioning
confidence: 99%
“…They would also have end-of-life care after disease progressed. We compared our prices with those from other similar cost-effectiveness studies conducted in China and the differences were moderate ( Dranitsaris et al, 2015 ; Zhang et al, 2019 ; Chen et al, 2021 ). Moreover, to make sure our prices were representative enough and account for uncertainties, we used a wide range of ±30% in the sensitivity analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Despite its clear efficacy, a potential limitation of SG use is represented by its cost. According to a recent analysis conducted in the United States and China, the price of SG should be at least halved to achieve cost-effectiveness [ 56 ]. This practical consideration poses relevant challenges in terms of drug’s accessibility, especially for those patients living in low-income countries.…”
Section: Discussionmentioning
confidence: 99%